The Influence of Psychological Capital and Learning Environment Toward SBM-ITB Students’ GPA - Tjakraatmadja, Jann Hidajat; Febriansyah, Hary (Jurnal Manajemen Teknologi, 2007)
Positive psychology (Psy –Cap= Psychology Capital), is the study on the strength and the excess of human mental factors that enables the growth of positive behaviors in the daily life as well as the work environment as a mean to reach welfare (well being). Psy-Cap approach is different from the Traditional Psychology approach with focuses on mental illness. Psy-Cap which has more preventive approaches has altered the orientation of the applications of modern psychology concepts to the environment and organizational field. This kind study is often refered as Positive Organizational Behavior (POB). This paper describes the research on the influence of Psy-Cap on the higher education world. In specific, the influence of the Psy-Cap and Learning Environment interaction to the relation between the National Adminission Test (SPMB) score and the Psycho-Test Score (IQ and EQ) toward the SBM-ITB students’ achievement index (GPA). The objects of this research are the SBM-ITB students (class of 2004). The data collecting method are through the opened and the closed questionnaires. The number of respondent is 110, however only 87 are valid. For data-processing, the statistical method ( reliabilities and validity test) and Structural Equation Modeling (SEM) were used.  The research found that: (1) The psycho test score (IQ and EQ) does not significantly influence the GPA; (2) The Psy-Cap factors of the students (hope state, optimism state, resiliency state, self efficiency, and subjective well being state) significantly influence the GPA; (3) not all interaction result of psy-cap and learning environment influence the GPA. This means some learning environment factors still do not have good qualities. (4) the good qualities of the learning environment factors in SBM are: computers and information technology, individual experiences, art, music, theatres, and friendship among students; (5) the less-good qualities of the learning environment factors in SBM are: library, lectures, experiences with lecturers and sponsor staffs, campus facilities, writing experience, club and organization, scientific and quantitative experience, topic of conversation, and source of information for the materials of conversation. Keywords: Positive Psychological Capital, Hope state, Optimism state, Resiliency state, Self efficiency, Subjective Well-Being state